An introduction to univariate GARCH models - Timo Teräsvirta (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
This paper contains a survey of univariate models of conditional heteroskedasticity. The classical ARCH model is mentioned, and various extensions of the standard GARCH model are highlighted. This includes the Exponential GARCH model. Stochastic volatility models remain outside this review.
Keywords: C22; 330; ARCH; conditional heteroskedasticity; GARCH; nonlinear GARCH; volatility modelling; Kapitalertrag; Prognoseverfahren; Volatilität; ARCH-Modell; Heteroskedastizität; Nichtlineares Verfahren; Theorie